Local Cisplatin Delivery in Mouse Reliably Models Sensorineural Ototoxicity Without Systemic Adverse Effects - Nacher-Soler, German; Lenglet, Sébastien; Coelho, Marta; Thomas, Aurélien; Voruz, François; Krause, Karl-Heinz; Senn, Pascal; Rousset, Francis (Frontiers in Cellular Neuroscience, 2021)
Cisplatin is a lifesaving chemotherapeutic drug with marked ototoxic adverse effects. Cisplatin-induced hearing loss affects a significant part of cancer-surviving patients and is an unmet clinical need with important socioeconomic consequences. Unfortunately, in current preclinical animal models of cisplatin ototoxicity, which are mainly based on systemic delivery, important morbidity is observed, leading to premature death. This methodology not only raises obvious animal welfare concerns but also increases the number of animals used in ototoxicity studies to compensate for dropouts related to early death. To overcome these important limitations, we developed a local delivery model based on the application of a cisplatin solution directly into the otic bulla through a retroauricular approach. The local delivery model reliably induced significant hearing loss with a mean threshold shift ranging from 10 to 30 dB, strongly affecting the high frequencies (22 and 32 kHz). Importantly, mice did not show visible stress or distress indicators and no significant morbidity in comparison with a traditional systemic delivery control group of mice injected intraperitoneally with 10 mg/kg cisplatin, where significant weight loss >10% in all treated animals (without any recovery) led to premature abortion of experiments on day 3. Mass spectrometry confirmed the absence of relevant systemic uptake after local delivery, with platinum accumulation restricted to the cochlea, whereas important platinum concentrations were detected in the liver and kidney of the systemic cisplatin group. A clear correlation between the cochlear platinum concentration and the auditory threshold shift was observed. Immunohistochemistry revealed statistically significant loss of outer hair cells in the basal and apical turns of the cochlea and an important and statistically significant loss of auditory neurons and synapses in all cochlear regions. In conclusion, local cisplatin delivery induces robust hearing loss with minimal morbidity, thereby offering a reliable rodent model for human cisplatin ototoxicity, reducing the number of animals required and showing improved animal welfare compared with traditional systemic models.